Dose-Dependent Effects of Aloin on the Intestinal Bacterial Community Structure, Short Chain Fatty Acids Metabolism and Intestinal Epithelial Cell Permeability - Gokulan, Kuppan; Kolluru, Pranav; Cerniglia, Carl E.; Khare, Sangeeta (Frontiers in Microbiology, 2019)
Aloe leaf or purified aloin products possess numerous therapeutic and pharmaceutical properties. It is widely used as ingredients in a variety of food, cosmetic and pharmaceutical products. Animal studies have shown that consumption of aloe or purified aloin cause intestinal goblet cell hyperplasia, and malignancy. Here, we tested antibacterial effects of aloin, against intestinal commensal microbiota. Minimum inhibitory concentration of aloin for several human commensal bacterial species (Gram-positive and Gram-negative) ranged from 1 to 4 mg/ml. Metabolism studies indicated that Enterococcus faecium was capable of degrading aloin into aloe-emodin at a slower-rate compared to Eubacterium spp. As a proof of concept, we incubated 3% rat fecal-slurry (an in vitro model to simulate human colon content) with 0.5, 1, and 2 mg/ml of aloin to test antimicrobial properties. Low aloin concentrations showed minor perturbations to intestinal bacteria, whereas high concentration increased Lactobacillus sp. counts. Aloin also decreased butyrate-production in fecal microbiota in a dose-dependent manner after 24 h exposure. The 16S rRNA sequence-data revealed that aloin decreases the abundance of butyrate-producing bacterial species. Transepithelial resistant result revealed that aloin alters the intestinal barrier-function at higher concentrations (500 μM). In conclusion, aloin exhibits antibacterial property for certain commensal bacteria and decreases butyrate-production in a dose -dependent manner. HIGHLIGHTS –Aloin exhibits antibacterial properties for certain intestinal commensal bacteria. –In rat fecal slurry (an in vitro model to simulate human colon content), longer aloin exposure (24 h) decreases the butyrate production in dose dependent manner. –The 16s rRNA sequencing data show that aloin decreased the abundance of butyrate producing bacterial species. –Rat intestinal commensal bacteria metabolized aloin into aloe-emodin. –Aloin altered the intestinal epithelial cells barrier integrity, however, the metabolic product of aloin - Aloe-emodin did not alter epithelial cells permeability.